ADOPSI INOVASI KELOMPOK WANITA TANI (KWT) TERHADAP PROGRAM PEKARANGAN PANGAN LESTARI (P2L) - Nina; Kusrini, Novira; Suyatno, Adi (Jurnal Pertanian Agros, 2025)
Limited agricultural land and changes in people's lifestyles have forced farmers to seek innovations to increase productivity and food security. The Sustainable Food Yard Program (P2L) is one of the innovations in overcoming problems, but its implementation has not been maximized. This study aims to examine the level of innovation adoption of women's farmer groups towards the Sustainable Food Yard Program (P2L) and identify factors that influence the achievement of innovation adoption. A total of 150 women farmers were selected as research respondents representing the population of women's farmer groups in Sebangki District, Landak Regency, West Kalimantan Province. A quantitative descriptive approach was used to analyze the level of innovation implementation and multiple linear regression methods to determine the factors that influence the success of innovation implementation. The results of the study showed that the level of innovation adoption towards the P2L program was still relatively low, while the factors that significantly influenced the level of innovation adoption were age and experience. Meanwhile, other factors such as education level, training participation, access to resources, and social support showed a positive relationship but did not have a significant influence in the context of this study.